Exploring Awareness, Knowledge, and Attitudes Regarding Tyre Safety Information among Commercial Drivers in Taraba State, Nigeria - Idi, Shadrach (ALSYSTECH Journal of Education Technology, 2024)
This research investigated the awareness, knowledge, and attitude to information concerning tyre safety use among commercial drivers in Taraba State, Nigeria. The study employed a mixed research method and focused on commercial drivers who are members of the National Union of Road Transport Workers (NURTW) in Taraba State. Data were gathered by administering a questionnaire to 360 respondents and three Focus Group Discussions (FGDs) with six members in each group. Descriptive statistics and thematic analysis were used for data analysis. The results show a high level of awareness regarding tyre inflation pressure (72.5%) and tyre tread information (71.4%) among the respondents. However, awareness levels are lower for regular tyre service, ageing information, and load and speed information. The primary sources of tyre safety information for the respondents are vulcanizers (33.6%), peers (21.6%), and tyre sellers (20%). However, knowledge about most aspects of tyre safety information is generally low, except for tyre tread and inflation pressure. Furthermore, the study revealed a negative attitude towards most aspects of tyre safety information, except for tyre tread and inflation pressure. The study recommended that the Federal Road Safety Corps (FRSC) enhance tyre safety awareness campaigns and monitoring in Taraba State using multi-channels of communication and targeting vulcanizers, tyre sellers, and opinion leaders such as NURTW officials and religious institutions.